Chancelloriid sclerites from the Lower Cambrian (Meishucunian) of eastern Yunnan, China, and the early history of the group. (2nd January 2014) - Moore, John L.; Li, Guoxiang; Porter, Susannah M.; Lane, Phil
Abstract Chancelloriids are a group of enigmatic sessile animals that are covered with sclerites shaped as rosettes of spines, producing an appearance like that of a barrel cactus. They are known only from Cambrian rocks. Isolated sclerites of chancelloriids are widespread in small shelly faunas, but they have proven difficult to treat taxonomically due to the variation within and between individual animals. We report on large samples of chancelloriid sclerites from the Meishucunian (pre‐trilobitic Lower Cambrian) of eastern Yunnan Province, China, including material from the Dahai Member of the Zhujiaqing Formation (the Zhujiaqing section, Dahai, Huize County) and the Shiyantou Formation (the Xiaotan section, Yongshan County). The material from the Dahai Member appears to come from a single species, Chancelloriella irregularis. Statistical analysis of morphotype co‐occurrences in different samples suggests that several species are represented in the material from the Shiyantou Formation, which we herein tentatively place in four species, Allonnia erromenosa, Allonnia tetrathallis, Archiasterella charma sp. nov. and Archiasterella cf. pentactina. We suggest therefore that careful study of large collections of isolated chancelloriid sclerites permits the identification of different species, opening the possibility of their use in evolutionary or stratigraphical studies. In particular, in South China, it seems that Chancelloriella irregularis is characteristic of rocks of the Paragloborilus subglobosus – Purella squamulosa Assemblage Zone and the Watsonella crosbyi Assemblage Zone, whilst Archiasterella and Allonnia first appear in the overlying Sinosachites flabelliformis – Tannuolina zhangwentangi Assemblage Zone. C. irregularis is thus amongst the oldest well‐characterized chancelloriids, and the irregularity and poor organization of its sclerites relative to those of younger forms support the hypothesis that chancelloriid sclerites are compound structures arising from the fusion of originally separate elements, perhaps homologous with sclerites of halkieriids and other coeloscleritophorans. The similarity between the arrangement of rays in a chancelloriid sclerite and the arrangement of bubbles in small bubble clusters suggests that in many cases, aspects of the form of chancelloriid sclerites are the result of simple physical processes.